Spatial Skills Associated With Block-Building Complexity in Preschoolers - Zhang, Xiaoxia; Chen, Chuansheng; Yang, Tao; Xu, Xiaohui (Frontiers in Psychology, 2020)
Block building is one of young children’s favorite play activities and is also used by psychologists to assess children’s intelligence. However, little research has attempted to systematically explore the cognitive bases of block building ability. The current study (N = 66 Chinese preschoolers, 32 boys and 34 girls; mean age = 4.7 years, SD = 0.29, range = 3.4 to 5.2 years) investigated the relationships between six measures of spatial skills (shape naming, shape recognition, shape composition, solid figure naming, cube transformation, and mental rotation; with the former four representing form perception and the latter two representing visualization) and block building complexity. Correlation results showed that three of the four measures of form perception (shape naming, shape recognition, and shape composition) were significantly and positively correlated with block building complexity, whereas the two measures of visualization were not. Results from regression models indicated that shape recognition and shape composition as well as shape-recognition-by-gender interaction were unique predictors of children’s block building complexity. These findings provide preliminary evidence for the basic spatial skills underlying children’s block building complexity and have implications for classroom instructions aimed at improving preschoolers’ block building complexity.